Fatherland : a memoir of war, conscience, and family secrets - Bilger, Burkhard (Random House, 2023)
"What do we owe the past? How to make peace with a dark family history? Burkhard Bilger hardly knew his grandfather growing up. His parents immigrated to Oklahoma from Germany after World War II, and though his mother was an historian, she rarely talked about her father or what he did during the war. Then one day a packet of letters arrived from Germany, yellowing with age, and a secret history began to unfold. Karl Gönner was a schoolteacher and Nazi party member from the Black Forest. In 1940, he was sent to a village in occupied France and tasked with turning its children into proper Germans. A fervent Nazi when the war began, he grew close to the villagers over the next four years, till he came to think of himself as their protector, shielding them from his own party's brutality. Yet he was arrested in 1946 and accused of war crimes. Was he guilty or innocent? A vicious collaborator or just an ordinary man, struggling to atone for his country's crimes? Bilger goes to Germany to find out"--